E‐TC: Development and pilot testing of a web‐based intervention to reduce anxiety and depression in survivors of testicular cancer. (22nd May 2017) - Heiniger, L.E.; Smith, A.B.; Olver, I.; Grimison, P.; Klein, B.; Wootten, A.; Abbott, J.‐A.M.; Price, M.A.; McJannett, M.; Tran, B.; Stockler, M.R.; Gurney, H.; et al.
Abstract : e‐TC is an online intervention designed to address common psychosocial concerns of testicular cancer survivors. It aims to reduce anxiety, depression and fear of cancer recurrence by providing evidence‐based information and psychological intervention. This paper details the development and pilot testing of e‐TC. During pilot testing, 25 men (with varying psychological profiles) who had completed treatment for testicular cancer, 6 months to 5 years ago (which had not recurred), used e‐TC over a 10‐week period and provided quantitative and qualitative feedback on the feasibility and acceptability of the programme. Six men also completed a qualitative interview to provide detailed feedback on their experiences using e‐TC. Fourteen men (56%) completed at least 80% of the programme. Participants reported a high level of satisfaction with the programme. Men's limited time was a barrier to programme use and completion, and participants suggested that men with a more recent diagnosis and a higher level of distress may be more likely to engage with the programme. e‐TC appears to be a feasible and acceptable online intervention for survivors of testicular cancer. Findings from this study are currently being used to refine e‐TC and guide the design of a larger efficacy study.